Forever strong - Drake, Piper J., 1976- (Drake, Piper J., 1976- True heroes novel., 2020)
Jiang Ying Yue assumed her kidnapping was random, that she was in the wrong place at the wrong time. After all, who would want to harm her? But then her rescuer---a charismatic former soldier who takes her breath away---uncovers a traitor in her father's organization. Now, Ying Yue realizes that she's become a pawn in a dangerous game, and her kidnapper won't be satisfied until she disappears for good. Zu Anyanwu's work with Search and Protect and his canine partner Buck have always been his first priority . . . until he's tasked with keeping Ying Yue safe. To him, the brave and resilient investment expert is more than just another client. But with danger closing in, Zu can't let his emotions get in the way of the most important job he's ever had---protecting the woman he loves.